Diffusion as Classification - Etzion, Dror (Organization Science, 2014)
An overlooked aspect of the diffusion of a practice in a population is the emergence of a de facto classificatory schema, distinguishing between actors that adopt a practice and those that do not. To investigate diffusion as classification, I develop a simulation model that highlights the conditions under which limited diffusion of practices leads to the emergence and entrenchment of classificatory schemas. The model depicts classification as a systemic phenomenon resulting from the interplay of actor-level micromotives and field-level macrobehaviors that jointly drive diffusion. Whereas extant theory on the origin of classificatory schemas emphasizes the role of agency, results from the model suggest that classificatory schemas can emerge somewhat unintentionally as practices diffuse. Moreover, by conceptualizing diffusion as classification, I suggest a means for disentangling the closely related and often conflated concepts of diffusion and institutionalization.